Multiple DSB Resection Activities Redundantly Promote Alternative End Joining-Mediated Class Switch Recombination - Sun, Xikui; Bai, Jingning; Xu, Jiejie; Xi, Xiaoli; Gu, Mingyu; Zhu, Chengming; Xue, Hongman; Chen, Chun; Dong, Junchao (Frontiers in Cell and Developmental Biology, 2021)
Alternative end joining (A-EJ) catalyzes substantial level of antibody class switching recombination (CSR) in B cells deficient for classical nonhomologous end-joining, featuring increased switch (S) region DSB resection and junctional microhomology (MH). While resection has been suggested to initiate A-EJ in model DSB repair systems using engineered endonucleases, the contribution of resection factors to A-EJ-mediated CSR remains unclear. In this study, we systematically dissected the requirement for individual DSB resection factors in A-EJ-mediated class switching with a cell-based assay system and high-throughput sequencing. We show that while CtIP and Mre11 both are mildly required for CSR in WT type cells, they play more critical roles in mediating A-EJ CSR, which depend on the exonuclease activity of Mre11. While DNA2 and the helicase/HRDC domain of BLM are required for A-EJ by mediating long S region DSB resection, in contrast, Exo1’s resection-related function does not play any obvious roles for class switching in either c-NHEJ or A-EJ cells, or mediated in an AID-independent manner by joining of Cas9 breaks. Furthermore, ATM and its kinase activity functions at least in part independent of CtIP/Mre11 to mediate A-EJ switching in Lig4-deficient cells. In stark contrast to Lig4 deficiency, 53BP1-deficient cells do not depend on ATM/Mre11/CtIP for residual joining. We discuss the roles for each resection factor in A-EJ-mediated CSR, and suggest that the extent of requirements for resection is context dependent.